SOCIALIZATION MODELS OF WASTE MANAGEMENT IN RURAL COMMUNITIES (A CASE STUDY OF THE COMMUNITY OF CILELES JATINANGOR) - Hermawati, Rina; Supangkat, Budiawati; Eko Nurseto, Hardian; Zakaria, Saifullah (LPPM Univ. Ibn Khaldun Bogor, 2023)
Waste is basically materials intentionally or unintentionally discarded as the product of human activities or natural processes. The handling and management of waste are increasingly more complex and complicated as its volume, types, and composition are more and more complex. Optimizing waste management needs an active role of the community to reduce, sort, and recycle the waste. However, the participation of the community in waste management often presents a complex challenge because it involves cultural, social, and economic factors. The community empowerment was conducted in Cileles Village, Jatinangor. Its proximate location to the center of education and economy gives Cileles Village the potential for the development of sustainable waste management. However, up to the present time, waste management in the village still faces some obstacles, such as the lack of infrastructure and the lack of the community’s motivation for sorting their waste. The result of this community service activity indicates that the community has a positive perception of waste and an awareness of waste management. However, the perception has not materialized in the community's daily behavior in managing their waste. For this reason, Socialization models of waste management have been carried out with participation, behavior change, and collaboration models.